Historical dictionary of South Africa - Saunders, Christopher C. 1943-; Limb, Peter (Rowman & Littlefield, 2020)
"This third edition of Historical Dictionary of South Africa contains a chronology, an introduction, and an extensive bibliography. The dictionary section has more than 600 cross-referenced entries on important personalities as well as aspects of the country's politics, economy, foreign relations, religion, and culture"--
Editor's Foreword -- Preface -- Reader's Note -- Abbreviations and Acronyms -- Maps -- Chronology -- Introduction -- THE DICTIONARY -- Bibliography -- About the Authors
Keywords: Geschichte; Südafrika; South Africa / History / Dictionaries; South Africa; Dictionaries; History; Wörterbuch